2016
DOI: 10.1080/09286586.2016.1235715
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Trachoma Mapping in Six Evaluation Units of Papua New Guinea

Abstract: Purpose: We sought to determine the prevalence of trachomatous inflammation – follicular (TF) in children aged 1–9 years, and trachomatous trichiasis (TT) in those aged ≥15 years, in suspected trachoma-endemic areas of Papua New Guinea (PNG). Methods: We carried out six population-based prevalence surveys using the protocol developed as part of the Global Trachoma Mapping Project. Results: A total of 19,013 individuals were sampled for inclusion, with 15,641 (82.3%) consenting to participate. Four evaluation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
1
16
2
Order By: Relevance
“…We found that younger children had lower odds of TF. This finding contrasts with that of many other studies, 19,21,26,27 where the burden of TF is typically found in pre-school childrenthe age group shown to harbor the bulk of the ocular C. trachomatis reservoir in environments in which this has been studied in detail. 28,29 A shift of the burden of TF to higher age groups has been noted in areas where trachoma has lower overall prevalence, presumably because intensity of transmission (and age of first exposure) is lower in these areas.…”
Section: Discussioncontrasting
confidence: 96%
“…We found that younger children had lower odds of TF. This finding contrasts with that of many other studies, 19,21,26,27 where the burden of TF is typically found in pre-school childrenthe age group shown to harbor the bulk of the ocular C. trachomatis reservoir in environments in which this has been studied in detail. 28,29 A shift of the burden of TF to higher age groups has been noted in areas where trachoma has lower overall prevalence, presumably because intensity of transmission (and age of first exposure) is lower in these areas.…”
Section: Discussioncontrasting
confidence: 96%
“…This is in keeping with the belief that younger children act as the reservoir of infection for ocular C. trachomatis, 16 and that close contact with more children is likely to facilitate spread.- [17][18][19][20] In addition, we found that unimproved latrine facilities, or living in a household with no latrine facilities, was an independent association of TF in children. Similar associations have been noted elsewhere, both prior to [21][22][23][24] and within the GTMP, 20,[25][26][27] and are in keeping with the belief that latrine facilities of a given standard limit the reproductive potential of the flies associated with transmission. 5,28,29 At larger scale, it is noted that active trachoma exists as a public health problem in Mozambique in an arc of endemicity stretching from Cabo Delgado in the country's north-east to Tete in the west.…”
Section: Discussionsupporting
confidence: 86%
“…Data from the Solomon Islands, 12 Vanuatu 13 and Papua New Guinea 14 have shown the epidemiology of trachoma in Melanesia to be unusual in that TT is rare or absent despite a moderate prevalence of TF. In contrast, in Kiribati, both TF and TT exceed the prevalence threshold for trachoma to be considered a public health problem.…”
Section: Introductionmentioning
confidence: 99%